A practical guide to cryptorchidism for the primary care physician - Lovin, Jennifer Margaret; Khater, Nazih; Mata, John A. (Family Medicine & Primary Care Review, 2019)
Cryptorchidism, also known as undescended testis, affects 3–5% of full term male infants at birth and 23% of preterm or low birth weight infants. Current guidelines recommend that all boys with cryptorchidism without testicular descent by 6 months of age be referred to an appropriate specialist for evaluation, with surgery preferably performed by 18 months. We aim to examine areas of controversy still being debated by reviewing published articles, in order to provide primary providers with a practical guide to diagnosis and management of the undescended testis. Our review examined published articles from 2000 to 2018, related to undescended testes, and their management. 32 articles were reviewed from 2000 to 2018 and showed with a high level of evidence that failure of testicular descent by 6 months of age (gestational) should prompt referral to an appropriate specialist. Physical exam is crucial. The main concerns for patients with cryptorchidism are the increased risk of testicular cancer and sub fertility. Routine use of scrotal ultrasound is not recommended in the evaluation of cryptorchidism. Diagnostic laparoscopy serves to confirm the presence of an intra-abdominal testicle. Surgical intervention within 18 months of age is imperative. Cryptorchidism should be corrected surgically between 6 months and 18 months of age. Early detection with diagnostic laparoscopy is the standard of care for treatment of palpable, undescended testis.